2018
DOI: 10.1111/bjd.16296
|View full text |Cite
|
Sign up to set email alerts
|

Development of an international core outcome set for peripheral vascular malformations: the OVAMA project

Abstract: Summary Peripheral vascular malformations (VMs) are birthmarks or swellings caused by the faulty development of blood vessels in the embryo. Different types are classified according to whether the components are mainly lymph vessels (LMs), veins (VMs) or combined arteries and veins (AVMs). It is hard to assess the various medical and surgical treatments available because there are no agreed methods for measuring the outcome. This international group carried out an on‐line survey of health professionals and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…The 9-point scale is recommended by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) working group to assess the importance of evidence and is the scale used in DelphiManager, a web-based system designed by the COMET Initiative for facilitating and managing Delphi surveys [2,21,22]. The 5-point rating scale was arbitrarily chosen as the comparator scale because it had been used previously in COS development Delphi studies [23][24][25], and because 5-point rating scales are relatively common across research studies that include a rating scale. Participants used the same rating scale they were initially allocated for all three Delphi rounds.…”
Section: Interventionmentioning
confidence: 99%
“…The 9-point scale is recommended by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) working group to assess the importance of evidence and is the scale used in DelphiManager, a web-based system designed by the COMET Initiative for facilitating and managing Delphi surveys [2,21,22]. The 5-point rating scale was arbitrarily chosen as the comparator scale because it had been used previously in COS development Delphi studies [23][24][25], and because 5-point rating scales are relatively common across research studies that include a rating scale. Participants used the same rating scale they were initially allocated for all three Delphi rounds.…”
Section: Interventionmentioning
confidence: 99%
“…For example, in a systematic review of the literature in atopic eczema, the authors found substantial heterogeneity in outcome measurement instruments used to measure disease severity . In vitiligo, similar variability in outcome reporting was found, and this is also the case for other dermatological diseases such as acne, hidradenitis suppurativa, psoriasis and vascular malformations …”
mentioning
confidence: 94%
“…5 In vitiligo, similar variability in outcome reporting was found, 6 and this is also the case for other dermatological diseases such as acne, 7 hidradenitis suppurativa, 8 psoriasis 9 and vascular malformations. 10 Using incomparable outcomes is considered a waste of valuable healthcare resources and is unwanted. 11 Moreover, for the majority of dermatological diseases, we do not know which outcomes are considered most important to patients and their healthcare providers.…”
mentioning
confidence: 99%
“…It has become an increasingly important outcome measure from a clinical and epidemiological point of view . An international multicentre consensus study, the Outcome Measures for Vascular Malformations project, suggested core outcome sets for clinical research on peripheral vascular malformations, including lymphatic malformations, venous malformations and arteriovenous malformations . It agreed that HRQoL should be a core outcome measure for all types of vascular malformations.…”
Section: Introductionmentioning
confidence: 99%